PENGARUH PUPUK KANDANG AYAM BERVARIASI DOSIS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogeae L.) PADA ENTISOL SIDERA - Sabran,Yosep Pata?dungan SogeH, Imam Wahyudi, Ilyas , (AGROTEKBIS, 2015)
A research has been done about chicken manure which aims to find out changes influence varied doses of chicken manure on the growth and yield of  peanut (arachies hypogeae) .  This study organized in a randomized block design with doses of chicken manure as follows control (without chicken manure), 2ton/ha,5ton/ha,7ton/ha,10ton/ha,12ton/ha  each treatment was repeated three times to obtain 18 experimental units.the experiment variables analiyzed by Anova and further test HSD,  Application of chicken manure with a dose of 12 tonnes effectively tested to increase result of the growth fo plant height, leaf number and weight of 100 seeds peanuts.